Assessment of Solar Panel Array Utilization Applied to a Fishing Vessel 20 GT - Rizky Irvana; Shanty Manullang (International Journal of Marine Engineering Innovation and Research, 2023)
Fishermen heavily depend on fossil fuels, around 95.4%, with no apparent decrease. Rising fuel costs and declining fossil fuel supplies challenge the fishing industry. The International Maritime Organization notes that ships using fossil fuels consume 277 million tons of fuel, contributing 2.5% to global emissions (961 million tons of CO2). TReducing reliance on fossil fuels and adopting alternative sources such as solar energy is suggested to address energy issues in Indonesia; solar energy, with an intensity of 0.6 to 0.7 kW/m2, is considered promising. This study uses an experimental design methodology to evaluate the installation of solar panels on a 20 GT fishing vessel at Muara Angke Port, Jakarta. Primary data, including ship size, was collected from the field. The economic focus is on the payback period, calculated through interviews with the crew. Exhaust gas emissions were calculated using factors established by the Ministry of Transportation. The results indicate that replacing CFL lamps with LED can save energy, specifically around 5 kW on this vessel. The feasibility of installing 14 solar panels is shown, costing over 20 years of Rp. 65,100,000. The payback period is estimated at three years, and the long-term analysis of Photovoltaic Solar Panels (PLTS) over additional engine investment. Cumulative emissions from the engine in one year are 155,007 tons, making PLTS environmentally beneficial without emissions.